2020
DOI: 10.1038/s41598-020-64068-3
|View full text |Cite
|
Sign up to set email alerts
|

Survival of pancreatic cancer patients is negatively correlated with age at diagnosis: a population-based retrospective study

Abstract: In this population-based retrospective study, we aimed to investigate the association between age at diagnosis and prognosis of pancreatic cancer (PC) patients using data from the National Cancer Institute’s Surveillance, Epidemiology, and the End Results database. Different factors for stratification, like race, sex, year of diagnosis, pathological grade, American Joint Committee on Cancer stage, historic stage, and tumour location, were included to compare the survival rates of patients of different age grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
40
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 28 publications
5
40
1
4
Order By: Relevance
“…The median overall survival (7.4 months) noted in this study compares favourably with a recent nationwide report from the Netherlands (3.8 months) 3 and previous reports from England and Wales (median survival less than 6 months) 40 . The negative impact of advancing age on survival noted in this study in patients above the age of 70 years supports the finding of a threefold increase in mortality from PDAC in patients above the age of 80 years in the National Cancer Institute's Surveillance, Epidemiology and the End Results database 41 …”
Section: Discussionsupporting
confidence: 85%
“…The median overall survival (7.4 months) noted in this study compares favourably with a recent nationwide report from the Netherlands (3.8 months) 3 and previous reports from England and Wales (median survival less than 6 months) 40 . The negative impact of advancing age on survival noted in this study in patients above the age of 70 years supports the finding of a threefold increase in mortality from PDAC in patients above the age of 80 years in the National Cancer Institute's Surveillance, Epidemiology and the End Results database 41 …”
Section: Discussionsupporting
confidence: 85%
“…It has been widely recognized that elderly patients’ internal environment (chronic inflammation and immune system dysfunction) is more likely to induce cancer under the stimulation of carcinogens [ 8 , 9 ]. Moreover, it has been reported that age is a significant negative prognostic factor for PC [ 10 ], and the immune system of elderly patients plays a key role in the development of PC [ 11 ]. Therefore, elderly patients may represent a distinct subgroup that needs more targeted clinical management plans [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to the report of epidemiology of pancreatic cancer [30],pancreatic cancer is mostly diagnosed in elderly individuals aged >70 years. Wang et al [31] proposed that age at diagnosis is a negatively independent factor to pancreatic cancer patients and early diagnosis means very important signi cance to improve the survival of pancreatic cancer patients .In one case report, Natesh et al [15] found that poorly differentiated signet ring cell carcinoma of pancreas was delayed because of incorrect diagnosis as chronic pancreatitis and patients died in 8 weeks after diagnosis, which means early diagnosis is important to the physician and the patient. In our analysis, the median age of pancreatic SRCC was 67 years (IQR,58.3-75.0 years),similarly to the previous literature.…”
Section: Discussionmentioning
confidence: 99%